2015
DOI: 10.1007/s11682-015-9405-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activity, cognitive function, and brain diffusion characteristics in old age

Abstract: The objective of this work was to test the hypotheses that a) more frequent cognitive activity in late life is associated with higher brain diffusion anisotropy and lower trace of the diffusion tensor, and b) brain diffusion characteristics partially mediate the association of late life cognitive activity with cognition. As part of a longitudinal cohort study, 379 older people without dementia rated their frequency of participation in cognitive activities, completed a battery of cognitive function tests, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…These results were consistent with previous findings . Education was found to be an important protective factor for MCI, and it could be explained by the concept of cognitive reserve, as people with a high level of education attainment were more likely to participate in cognitive activities, such as reading, which helps enhance one or more brain properties and contributes to cognitive reserve . Physical activity was also found to be a protective factor for MCI.…”
Section: Discussionsupporting
confidence: 91%
“…These results were consistent with previous findings . Education was found to be an important protective factor for MCI, and it could be explained by the concept of cognitive reserve, as people with a high level of education attainment were more likely to participate in cognitive activities, such as reading, which helps enhance one or more brain properties and contributes to cognitive reserve . Physical activity was also found to be a protective factor for MCI.…”
Section: Discussionsupporting
confidence: 91%
“…The link between cognitive activity and cognitive functioning is consistent with the "use it or lose it" hypothesis, which 820 N. Sharifian et al states that engaging in cognitively stimulating activities, such as playing board games and attending lectures, may help to preserve cognitive functioning and promote cognitive reserve, whereas disuse can lead to deterioration of cognitive skills (Hultsch, Hertzog, Small, & Dixon, 1999;Reed et al, 2011). Cognitively stimulating activities may maintain cognition through their impact on brain structure and function, such as white matter integrity (Arfanakis et al, 2016) and synaptic plasticity (Buitenweg, Murre, & Riddenrinkhof, 2012). For example, in an intervention study, older adults who engaged in a strategy-based real-time video game over 7-8 weeks demonstrated improvements in executive functioning compared to the no-contact control group (Basak, Boot, Voss, & Kramer, 2008), suggestive of the protective effects of cognitive activity for cognition.…”
Section: The Benefits Of Cognitive and Physical Activity For Cognitionsupporting
confidence: 57%
“…Further, late-life cognitive activity was not related to common neuropathologies [181]. However, it was related to brain microstructure by neuroimaging, which partially mediated the association of cognitive activity with level of cognition [182]. We also found that total daily physical activity measured by actigraphy was associated with risk of AD dementia [183] and negative social interactions were associated with incident cognitive impairment [184].…”
Section: Resultsmentioning
confidence: 99%